Long-term cold, freezing and drought: overlapping and specific regulatory mechanisms and signal transduction in tea plant (Camellia sinensis (L.) Kuntze) - Samarina, Lidiia; Wang, Songbo; Malyukova, Lyudmila; Bobrovskikh, Alexandr; Doroshkov, Alexey; Koninskaya, Natalia; Shkhalakhova, Ruset; Matskiv, Alexandra; Fedorina, Jaroslava; Fizikova, Anastasia; Manakhova, Karina; Loshkaryova, Svetlana; et al. (Frontiers in Plant Science, 2023)
Low temperatures and drought are two main environmental constraints reducing the yield and geographical distribution of horticultural crops worldwide. Understanding the genetic crosstalk between stress responses has potential importance for crop improvement. Resequencing of new germplasm outside of the global producing regions can help to discover the novel molecular mechanisms of acclimation and domestication of woody crops in the extremal climatic zones. In this study, Illumina RNA-seq and Pac-Bio genome resequencing were used to annotate genes and analyze the transcriptome dynamics in tea plant under the long-term cold, freezing and drought. The highest number of differentially expressed genes (DEGs) were identified under long-term cold (7896) and freezing (7915) with 3532 and 3780 upregulated genes, respectively. The lowest number of DEGs was observed under 3-days Drought (47) and 9-days Drought (220), with 5 and 112 genes upregulated, respectively. The Recovery after cold had 6.5 times greater the DEGs number as compared to drought Recovery. Only 17.9 % of the cold-induced genes were also upregulated by drought. In total, 1492 transcription factor genes related to 57 families were identified. However, only 20 transcription factor genes were commonly upregulated by the cold, freezing and drought. Among 232 common upregulated DEGs, most were related to the signal transduction, the cell wall remodelling and the lipid metabolism. Co-expression analysis and network reconstruction showed 19 genes with the highest co-expression connectivity: seven genes are related to the cell wall remodeling (GATL7, UXS4, PRP-F1, 4CL, UEL-1, UDP-Arap, TBL32), four genes of Ca2+-signaling (PXL1, Strap, CRT, CIPK6), three genes related to photo-perception (GIL1, CHUP1, DnaJ11), two genes of hormone signaling (TTL3, GID1C-like), two genes of ROS signaling (ERO1, CXE11) and one gene of phenylpropanoid pathway (GALT6). Based on our results, the several important overlapping mechanisms of long-term stress responses include the cell wall remodeling through lignin biosynthesis, o-acetylation of polysaccharides, pectin biosynthesis and branching, xyloglucan and arabinogalactan biosynthesis. This study provides a new insight into the long-term stress responses in woody crops and a set of new target candidate genes were identified for the molecular breeding aimed at tolerance to abiotic stresses.